The Whispering Room : Jane Hawk #2 - Koontz, Dean R. 1945- (Dean Ray) (New York : Bantam Books, 2018)
events as it is audacious. amongst Dean Koontz's finest contemporary work."--Mystery Scene "A proven specialist in action scenes, Koontz pulls off some doozies here. The book is full of neat touches. And the prose, as always in a Koontz novel, is first-rate. Perhaps Koontz's leanest, meanest thriller, this initial entry in a new series introduces a smart, appealing heroine who can outthink as well as outshoot the baddest of bad dudes."--Kirkus Reviews (starred review) "The latest page-turner by Dean Koontz introduces readers to Jane Hawk. An inspired choice for a protagonist. action, zippy dialogue and a winning character at the center of the book, part of a new series by Koontz."--Minneapolis Star-Tribune "Long an A-list bestseller, Koontz has always delivered the goods. [His] varied bibliography now adds a new series and an exciting new heroine."--Booklist "Fantastically written (as always by Mr. Koontz). You are riveted on page one. 5 stars!"--Suspense Magazine"--.
events as it is audacious. amongst Dean Koontz's finest contemporary work."--Mystery Scene "A proven specialist in action scenes, Koontz pulls off some doozies here. The book is full of neat touches. And the prose, as always in a Koontz novel, is first-rate. Perhaps Koontz's leanest, meanest thriller, this initial entry in a new series introduces a smart, appealing heroine who can outthink as well as outshoot the baddest of bad dudes."--Kirkus Reviews (starred review) "The latest page-turner by Dean Koontz introduces readers to Jane Hawk. An inspired choice for a protagonist. action, zippy dialogue and a winning character at the center of the book, part of a new series by Koontz."--Minneapolis Star-Tribune "Long an A-list bestseller, Koontz has always delivered the goods. [His] varied bibliography now adds a new series and an exciting new heroine."--Booklist "Fantastically written (as always by Mr. Koontz). You are riveted on page one. 5 stars!"--Suspense Magazine"--
Keywords: FICTION / Suspense; FICTION / Action & Adventure; FICTION / Psychological; Suspense fiction; Psychological fiction